Instrumentalization of naturalism in Nietzsche’s anthopological reflection - Misztal, Dawid (Hybris, 2016)
The paper presents anthropological issues as one of the main topics of Nietzsche’s philosophy. I begin with how Nietzsche defines the goals of his anthropological reflection and then I identify the perspective of naturalism as its central interpretational tool. Subsequently I try to show how it is instrumentalized in order to develop correct – according to Nietzsche – characteristics of human being, and as a mean of Nietzsche’s critique of metaphysics. In this way conceiving man as “homo natura” allows to reflect on human in axiological context not limited by old metaphysical beliefs. This attempt of combining naturalistic dimension with axiological one determines specific character and importance of Nietzsche’s anthropology.